Assessment of the feed additives consisting of potassium iodide and calcium iodate anhydrous for all animal species for the renewal of their authorisation (AJAY EUROPE SARL) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Roberto Edoardo Villa; Giovanna Azimonti; Eleftherios Bonos; Henrik Christensen; Mojca Durjava; Birgit Dusemund; Ronette Gehring; Boet Glandorf; Maryline Kouba; Marta López‐Alonso; Francesca Marcon; et al. (EFSA Journal, 2025)
Abstract Following a request from the European Commission, EFSA was asked to deliver a scientific opinion on the safety and efficacy of potassium iodide (3b201) and calcium iodate anhydrous (3b202) as nutritional additives (functional group: compounds of trace elements) for all species and categories. The additives are currently authorised for use in all animal species. The applicant has provided evidence that both additives, potassium iodide and calcium iodate anhydrous, comply with the conditions of the authorisation. The Panel on Additives and Products or Substances used in Animal Feed (FEEDAP Panel) confirms that the use of potassium iodide and calcium iodate anhydrous under the current authorised conditions of use are safe for the target species and the environment. Due to the lack of adequate deposition data to assess the consumer exposure, the FEEDAP Panel is not in the position to conclude on the safety for the consumer. With regard to the safety of users, potassium iodide is not an eye irritant, but calcium iodate anhydrous is. The additives potassium iodide and calcium iodate anhydrous should be considered skin and respiratory sensitisers. Inhalation and dermal exposure are considered a risk. There is no need for assessing the efficacy of the additive in the context of the renewal of the authorisation.